A class of location invariant estimators for heavy tailed distributions. Issue 3 (1st February 2023) - Zhang, Lvyun; Chen, Shouquan
Abstract: In this paper, a new class of location-invariant semi-parametric estimators of a positive extreme value index γ > 0 is proposed. Its asymptotic distributional representation and asymptotic normality are derived, and the optimal choice of the sample fraction by mean squared error is also discussed for some special cases. Finally comparison studies are provided for some familiar models by Monte Carlo simulations.